The Influence Of War On The Future Generations Reflected In Nathalie Abi-Ezii's A Girl Made Of Dust (2008): A Sociological Approach - Trengginas, Gelar, Dr. M. Thoyibi, M. S., Mauly Halwat Hikmat, Ph.D (2015)
The major problem in this study is how influence of war on the children social life in West Asia society is reflected in Nathallie Abi- Ezzi's A Girl Made of Dust. The objectives of the study are finding the stuctural elements and analyzing the aspects of The Influence Of War On The Future Generation in West Asia society in the early twenty first century based on sociological theories. In analyzing the novel, the writer uses qualitative research whose data are based on primary sources, Nathallie A Girl Made of Dust by Nathallie Abi-Ezzi released 2008, and secondary sources, such as: Swingewood's sociology, Nathallie Abi-Ezzi's biography, internet, and the other data related to the research. In analyzing the data, she employes and applies some approaches. Structural analysis approach is used to analyze the elements of the novel. The Sociological approach is used to analyze the relation between the novel and the social condition of West Asia in the early twenty first century, later continued by applying sociological theory. These approaches are employed in order to have the appropriate analysis and to answer the problems. The result of analysis confirms that there is a close relation between this novel and the social reality in West Asia in the early twenty first century which the social condition is not so good. Civil war between Palestinians and Israelis strongly influence their social conditions. Based on structural analysis, Nathallie adopted from major character Ruba Khouri, 8 years old. She does not really understand the civil war, but she can feel of impact involving emotion in herself. Nathellie also make the story fully dramatic and tragic and used the style which is very easy to understand.